2016
DOI: 10.14716/ijtech.v7i4.2798
|View full text |Cite
|
Sign up to set email alerts
|

Intercity Mode Choice Modelling: Considering the Intracity Transport Systems with Application to the Jakarta-Bandung Corridor

Abstract: The choice among modes of intercity transport depends on conditions of not only intercity transport modes but also intracity transport in both the departure city and the arrival city. Intracity transport conditions might be advantageous for one intercity mode and disadvantageous for others. Intercity and intracity transport conditions are complex and need to be approached systemically. This study proposes an approach based on the passengers' preferences. The logit model was adapted to evaluate the transport mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
2
3
0
Order By: Relevance
“…The main objective of this study is to review the previous Jakarta -Surabaya HSR demand forecast, develop a new choice of mode model, and update the forecast. In this study, access and egress to and from HSR stations are represented explicitly by distance and cost parameters, which complement previous studies such as Barus et al (2016), who found that access to stations was very important to improve the competitiveness of inter-city transportation, although it was still qualitative.…”
Section: Introductionsupporting
confidence: 68%
“…The main objective of this study is to review the previous Jakarta -Surabaya HSR demand forecast, develop a new choice of mode model, and update the forecast. In this study, access and egress to and from HSR stations are represented explicitly by distance and cost parameters, which complement previous studies such as Barus et al (2016), who found that access to stations was very important to improve the competitiveness of inter-city transportation, although it was still qualitative.…”
Section: Introductionsupporting
confidence: 68%
“…Passengers on the Jakarta-Bandung trip are less sensitive to ticket fare, while the opposite is true for Bandung-Jakarta. This finding is similar to that of previous research by Barus et al (2016). Moreover, car users with more than one passenger are less interested in using HST since traveling in a large group by car is still easier and cheaper than using HST, although there is the added uncertainty of travel time due to the unpredictability of traffic conditions.…”
Section: Demand Analysissupporting
confidence: 89%
“…The stakeholder needs to consider the travel time, level of comfort, and accessibility in order to define the optimum price (Avineri & Bovy, 2008;Barus et al, 2016). The train will take approximately 50 minutes from Jakarta (Halim) to Bandung (Gedebage), with two intermediate stops in Karawang and Walini.…”
Section: High-speed Trainmentioning
confidence: 99%
“…A logistic regression model is an appropriate procedure for describing the effect of several numbers of categorical or continuous explanatory variables on the probability of occurrences of a dichotomous outcome variable (Peng et al, 2002). Logistic regression has been applied in many different areas, such as in medicine (Yusuff et al, 2012;Zangmo & Tiensuwan, 2018), engineering (Barus et al, 2016), and social sciences (Ramosacaj et al, 2015). However, most follow-up studies have more than one type of event; thus, the traditional logistic model is no longer suitable for use.…”
Section: Methodsmentioning
confidence: 99%